Analysis of Indonesia's Nutritional Status Survey Results 2021–2022: Trend of Stunting Prevalence Rates in the Provinces of South Sumatera and Bengkulu Towards a National Target of 14% in 2024 - Muhammad Ridho Nugroho; Erwin Armeidi; Meriwati Mahyuddin (Indonesian Journal of Health Research and Development, 2023)
This paper aims to examine the development trend of the prevalence of stunting in the provinces of South Sumatra and Bengkulu between 2021-2022, by exploring the PB/U and TB/U indicators to see trends in the prevalence of stunting in regencies and cities in the two provinces. The study method uses a secondary data analysis approach to the results of the Indonesian Nutrition Status Survey which will be conducted from 2021 to 2022, using descriptive statistical analysis. The sample studied was the results of a nutritional status survey in the Provinces of South Sumatra and Bengkulu in 27 urban districts. The results of the study in general show that there has been a decline in the stunting prevalence rate from 2021-2022 in the South Sumatra Province by 6.2% and the Bengkulu Province by 2.3%. However, if we look at the figures per district/city, there is one district in South Sumatra Province which has experienced an increase in the prevalence of stunting, namely Banyu Asin by 2.8% and there are five districts in Bengkulu Province which have also experienced an increase in the prevalence of stunting, namely Kepahiang by 2%, South Bengkulu 2.4%, North Bengkulu 2.1%, Mukomuko 0.1%, Kaur 1.1%. Based on the results above, it can be concluded that the prevalence of stunting in the provinces of South Sumatra and Bengkulu in general has decreased, but there are 6 districts in the two provinces that are still experiencing an increase in the prevalence of stunting. It is suggested to the competent authorities in the 6 regencies to improve specific nutrition interventions and sensitive nutrition interventions by means of convergence between regional apparatus organizations (OPD) through the Team for the Acceleration of Stunting Reduction (TPPS) in each city-district.